Arteriovenous shunt as the best hemodialysis access in Chronic Kidney Disease (CKD) patients: a literature review - Abed Nego Okthara Sebayang; Niko Azhari Hidayat (Indonesian Vascular Access Association (IVAA), 2021)
Arteriovenous Shunt (AV Shunt) is a minor surgical operation that connects (creating anastomoses) the arteries and veins in the arm or other body part for the purpose of making connection access for hemodialysis. AV shunt is the primary choice in establishing vascular access for hemodialysis in patients with Chronic Kidney Disease (CKD). Therefore, this study aims to review the arteriovenous shunt as a hemodialysis access option in CKD patients. The literature study was conducted by searching various written sources, whether in the form of books, archives, articles and journals, or documents relevant to the problem being studied. The mortality rate after AV shunt is 0%, even though it still has postoperative complications. Based on the location of the operation, making the AV shunt is prioritized on the distal part that is not dominant to minimize the damage to the AV shunt. The location of the wrist, namely the brachiocephalic, is a top priority in making an AV shunt because it has many advantages. AV shunt is the primary choice of vascular access for hemodialysis in patients with chronic kidney disease. It is hoped that through the AV shunt, the life expectancy of patients with CKD can be increased, and patients with CKD must receive support from other disciplines such as interns, psychologists, and the patient's family.